2023
DOI: 10.1007/s00227-023-04312-2
|View full text |Cite
|
Sign up to set email alerts
|

Stay here, but keep quiet: the effects of anthropogenic noise on Guiana dolphins (Sotalia guianensis) in southeastern Brazil

Israel Maciel,
Teresa Belderrain,
Maria Alice S. Alves
et al.

Abstract: Shipping is the principal source of anthropogenic noise in the aquatic soundscape of coastal areas.Noise can have temporary or permanent effects on the physiology, behavior, and ecology of the marine mammals and, as noise pollution is considered to be an important threat to Guiana dolphins (Sotalia guianensis), we focused on this question in the present study. We modeled the impacts of anthropogenic noise on the acoustic behavior and distribution of these dolphins. We considered the acoustic parameters and occ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 103 publications
0
4
0
Order By: Relevance
“…Foraging in areas occupied by vessels may mask dolphin communications, which are essential for the coordination of the group's movements when catching prey [55]. A previous study in Sepetiba Bay [17] found that Guiana dolphins communicated significantly less in noisier areas. Dolphins in poor condition may prefer to conserve energy by avoiding communication rather than spending more energy to increase vocalization emission rates, even if this may affect their feeding success [43].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Foraging in areas occupied by vessels may mask dolphin communications, which are essential for the coordination of the group's movements when catching prey [55]. A previous study in Sepetiba Bay [17] found that Guiana dolphins communicated significantly less in noisier areas. Dolphins in poor condition may prefer to conserve energy by avoiding communication rather than spending more energy to increase vocalization emission rates, even if this may affect their feeding success [43].…”
Section: Discussionmentioning
confidence: 97%
“…The large proportion of individuals photo-identified in a poor condition is a preoccupying reflection of the health status of this dolphin population [3]. The poor condition of the dolphins is likely a consequence of the cumulative impacts on these animals over the past decade in Sepetiba Bay, resulting from overfishing, excessive tourism, and noise, chemical, and organic pollution [17,37]. It is important to note, however, that this dataset includes transient individuals, which may be less exposed to these impacts than the resident dolphins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this scenario, strategic approaches that link science to aspects of daily life can be a powerful and useful instrument. Some basic examples include framing or relating climate change to air pollution (Hart and Feldman, 2021) or exploring how noise and water pollution affect the lives of marine animals, such as dolphins and other mammals inhabiting ecosystems near urban centers (Maciel et al, 2023;Alzola-Andres et al, 2024). Thus, incorporating media literacy and emphasizing real-world connections offers a pragmatic pathway forward.…”
Section: The Intersection Between Scientific Research and Its Public ...mentioning
confidence: 99%